Minimum bactericidal concentration of ciprofloxacin to Pseudomonas aeruginosa determined rapidly based on pyocyanin secretion - Liu, Yi; Moore, John H.; Kolling, Glynis L.; McGrath, John S.; Papin, Jason A.; Swami, Nathan S. (Sensors and actuators. B, Chemical, 2020)
[Display omitted] •Pyocyanin as a marker for determining bactericidal deactivation of P. aeruginosa.•Nanoporous gold for electrochemical detection of pyocyanin in biological matrices.•Rapidly determines ciprofloxacin level for bactericidal deactivation of P. aeruginosa.•Bacterial persistence at minimum inhibitory levels detected without prolonged culture. Infections due to Pseudomonas aeruginosa (P. aeruginosa) often exhibit broad-spectrum resistance and persistence to common antibiotics. Persistence is especially problematic with immune-compromised subjects who are unable to eliminate the inhibited bacteria. Hence, antibiotics must be used at the appropriate minimum bactericidal concentration (MBC) rather than at minimum inhibitory concentration (MIC) levels. However, MBC determination by conventional methods requires a 24 h culture step in the antibiotic media to confirm inhibition, followed by a 24 h sub-culture step in antibiotic-free media to confirm the lack of bacterial growth. We show that electrochemical detection of pyocyanin (PYO), which is a redox-active bacterial metabolite secreted by P. aeruginosa, can be used to rapidly assess the critical ciprofloxacin level required for bactericidal deactivation of P. aeruginosa within just 2 h in antibiotic-treated growth media. The detection sensitivity for PYO can be enhanced by using nanoporous gold that is modified with a self-assembled monolayer to lower interference from oxygen reduction, while maintaining a low charge transfer resistance level and preventing electrode fouling within biological sample matrices. In this manner, bactericidal efficacy of ciprofloxacin towards P. aeruginosa at the MBC level and bacterial persistence at the MIC level can be determined rapidly, as validated at later timepoints using bacterial subculture in antibiotic-free media.